Effectiveness of Equal-Age Counselling Services to Prevent Early Marriage Attitude of Class IX MTS students Riyadhus Sholihin Sunggal - Layla Suci Ramadhani; M Fauzi Hasibuan (Universitas Muhammadiyah Enrekang, 2024)
The study aims to find out the effectiveness of peer counselling services to prevent attitudes towards early marriage of students of 9th grade MTS Riyadhus Sholihin Sunggal. The research method used is experimental. In this study the researchers used the Pre Experimental research model using One Group Pre Test – Post Test Design. As to the data collection techniques used are (1) document analysis, namely list of names, number of students of class IX MTS Riyadhus Sholihi Sunggal and photo documentation of the research. (2) The test method used in this study is the filling of angket. (3) Observation, from the results of the analysis of data of counselling services for prevention of early marriage attitudes in students using the statistical analysis technique t-test, obtained t_count as 5.542 while the size of the number on the table of value t for one-party test (one tail test) with a degree of significance of 0.05 (5%) at d.b N-1= 9 is 1.833. Therefore, the result of the data analysis of 5,542 is above the limit of rejection of the zero hypothesis which is large 1,833 (t_count > t_table), so this study is significant.